Temporal Variability in Survival of Non-Breeding Northern Bobwhites in Ohio - Adam K. Janke; Robert J. Gates (National Quail Symposium Proceedings, 2017)
Non-breeding season survival is an important determinant of population growth rates of northern bobwhites (Colinus virginianus) and is primarily influenced by hunter harvest, predation, and weather. The collective influence of these factors varies within and among years and across the bobwhite range. Understanding factors that influence variation in survival is important to inform regionally-specific management strategies for declining bobwhite populations. We radiomarked 311 bobwhites from 73 coveys to investigate temporal variation in non-breeding season (Oct-Mar) survival of a declining bobwhite population on private land in southwestern Ohio during 2008–2011. We used the data bootstrapping feature in Program MARK to adjust for overdispersion caused by dependency of survival among members of the same covey. Temporal variation in survival was best modeled (wi 1⁄4 0.935) with weekly differences in survival rates that varied within and between years. There was only slight dependency in survival due to covey affiliation between the 2 seasons (median cˆ 1⁄4 1.51). Non-breeding season survival was low (Sˆ 2009–2010 1⁄4 0.05, 95% CI 1⁄4 0.03-0.11, Sˆ 2010–2011 1⁄4 0.12, 95% CI 1⁄4 0.07- 0.20) in 2 years with data for the entire season. Survival during 10 December-31 March varied among the 3 years (Sˆ2008–2009 1⁄4 0.45, 95% CI 1⁄4 0.29-0.61, Sˆ2009–2010 1⁄4 0.11, 95% CI 1⁄4 0.05-0.21, Sˆ2010–2011 1⁄4 0.25, 95% CI 1⁄4 0.17-0.34). There were 2 periods of low survival; a short period in early fall that coincided with senescence of herbaceous vegetation and the hunting season, and during periods with prolonged snow cover during winter. Late winter survival during periods of snow cover was most variable and winter severity appeared to have the greatest influence on seasonal survival during our study. Management strategies to improve non-breeding season survival in northern populations should focus on managing winter habitat to improve survival during periods of prolonged snow cover.
Keywords: Colinus virginianus; harvest; known-fates model; northern bobwhite; Ohio; overdispersion; Program MARK; survival; winter weather